CFD analysis of flashing flow in two-phase geothermal turbine design. Issue 2 (30th March 2020) - Rane, Sham; He, Li
Abstract: A thermal power plant for the East African Rift countries is under study for combined energy and freshwater generation using geothermal water, available at above 500 kPa pressure and temperature exceeding 150°C. This article presents the computational fluid dynamics (CFD) model and analysis of the two-phase turbine used for power generation in this total flow thermal plant. Flash boiling was implemented using a two-fluid multiphase model with the thermal phase-change criteria for heat, mass, and momentum transfer in the CFD solver ANSYS CFX. Initially, flashing flow in a converging–diverging nozzle was validated. This stationary nozzle model was then extended to a curved rotating nozzle reaction turbine and the results of flow and power were evaluated against available test data at 400 kPa feed water pressure under subcooled condition of 117°C and a very low backpressure of 6 kPa. Flow through this turbine was predicted within 8% deviation. An overestimate in thermodynamic power by 30–50% was predicted at speeds below 4000 rpm, while at the design speed of 4623 rpm the deviation was less than 5%. Rotor torque and hence power estimate was found to be dependent on the bubble size, bubble number density, and heat transfer parameters prescribed in the CFD model. The vapour dryness fraction at turbine exit was close to an isentropic expansion vapour quality. The isentropic efficiency was 7.5–17% for the analysed speed range. Graphical Abstract: